Fs-Time Resolved Microscopy as a tool for monitoring laser-matter interaction - Carrasco-García, Irene María (My University, 2015)
Femtosecond laser pulses provides the advantage in comparison with longer pulses that there is no interaction between laser and plasma. Moreover, the applied energy is deposited in much less time than nanosecond pulses, for example, which implies that plasma related phenomena will take place at different time scales, and present different ablation characteristics. We present a tool for monitoring laser-matter interaction using femtosecond pulses and a explanation of the related phenomena for improving plasma analysis.
Keywords: Láseres de femtosegundos